2016
DOI: 10.1161/circep.115.003879
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Isolation Area During the Chronic Phase After a 28-mm Second-Generation Cryoballoon Ablation Demarcated by High-Resolution Electroanatomic Mapping

Abstract: Background-The post-second-generation cryoballoon (CB) ablation isolation area during the chronic phase has not been described. The aim of this study was to quantitatively evaluate the chronic-phase isolation area after 28-mm secondgeneration CB ablation and compare it to the estimated conventional radiofrequency circumferential pulmonary vein isolation (CPVI) line. Methods and Results-Thirty-two patients with paroxysmal atrial fibrillation underwent pulmonary vein (PV) isolation using second-generation CB. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 21 publications
(30 reference statements)
8
65
2
Order By: Relevance
“…Second, repeat procedures were not analyzed to assess long-term durability of the PVI. Although some differenc-es can be expected in the chronic phase, the trends should be similar to those in the acute phase 28,29) .…”
Section: Limitationmentioning
confidence: 84%
See 1 more Smart Citation
“…Second, repeat procedures were not analyzed to assess long-term durability of the PVI. Although some differenc-es can be expected in the chronic phase, the trends should be similar to those in the acute phase 28,29) .…”
Section: Limitationmentioning
confidence: 84%
“…Recent studies comparing CF-guided RFA with CBA have shown statistical equivalence between the 2 technologies 25) . This may relate to the fact that even focused lesions may eliminate triggers and that not for all transmural continuous lesions around the PVs are needed [26][27][28][29] .…”
Section: Impact Of Different Technique Of Cb Ablation Vsmentioning
confidence: 99%
“…A previous study showed the posterior left atrial (LA) wall area isolated by CBA to be wide and antral, and the resulting debulking of this area, in addition to discrete PVI, was thought to explain, at least in part, the efficacy of CBA 7) . However, a more recent study showed the PV antral area isolated by CBA to be significantly smaller than the circumferential PV area isolated by RFA 8) . The intrinsic cardiac autonomic nervous system (i.e., the ganglionated plexi [GPs]) has been thought to contribute to the AF substrate and specifically to the initiation and persistence of AF [9][10][11] .…”
Section: Introductionmentioning
confidence: 89%
“…A three‐dimensional mapping system was used as a reference to determine the location of the circular mapping catheter to identify the PV reconnection site and to measure the isolation area before starting repeat ablation (Figure ). The isolated surface areas of each PV antrum and ipsilateral PV antrum were calculated …”
Section: Methodsmentioning
confidence: 99%
“…However, large PVs will allow the advancement of the CB distally while the PV roof, antrum, and left atrial anterior/posterior wall near the PV junction remain intact. This means that CB ablation isolates a limited PV area . We hypothesized that a wide ablation area will eliminate more arrhythmic foci and lead to better outcomes.…”
Section: Introductionmentioning
confidence: 99%